Dinamika Perubahan Garis Pantai Di Muara Gembong, Bekasi, Jawa Barat Pada Tahun 2011-2021 - Meizwar, Dara Afiifah; Tarya, Ayi (Journal of Tropical Marine Science, 2024)
Shoreline change can be an increase (accretion) or decrease (abrasion) of land on the coast due to human activities. This research aims to determine shoreline change occurs at Muara Gembong in 2011-2021 using coastline extracted from Landsat satellite imagery with band ratio and composite RGB methods. Shoreline changes were analyzed with Digital Shoreline Analysis (DSAS) using Net Shoreline Movement (NSM), End Point Rate (EPR), and Linear Regression Rate (LRR) statistical methods, to identify distance and rate of coastline change. Muara Gembong area is divided into Zone A located in the south and Zone B located in the north which is directly exposed to the Java Sea. Shoreline change for 10 years showed a tendency to accrete as far as 6.81 m. Rate of shoreline change value 0.18 m/year with accretion rate 12.24 m/year and abrasion rate -7.68 m/year. The total area of abrasion in 10 years comes to 805,562.41 m2 and the area of accretion is 881,897.24 m2. The direction of sediment transport in Zone A leads to the south or to the left of estuary, while in Zone B heading east or right of estuary. It is influenced by the greatest contribution of wave energy that propagates from the northwest.